Prospective analysis of gait characteristics in chronic inflammatory demyelinating polyradiculoneuropathy. (October 2020) - Bozovic, I.; Peric, S.; Basta, I.; Rakocevic-Stojanovic, V.; Lavrnic, D.; Stevic, Z.; Radovanovic, S.
Highlights: Most gait parameters show significant differences when compared between CIDP and HC. Findings in CIDP were shorter SL, prolonged CT and DST and increased CV of SL and ST. Several gait parameters (CVs of CT, SL, ST and DS) correlated with patients' age. After 6-month follow up INCAT score improved in nine and MRC improved in 8 patients. Changes of CT differentiated patients with improved vs. non-improved INCAT scores. Abstract: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a disorder that may lead to functional impairment, including gait abnormalities. Our aim was to analyze gait characteristics in patients with CIDP compared to healthy controls (HC). Moreover, we sought to determine changes of gait parameters after six-month follow-up period. Twenty-four patients with CIDP and 24 HCs performed basic walking task, dual-motor task, dual-mental task, and combined task using the same GAITRite system. Lower limb MRC-SS and lower limb INCAT disability score were assessed. Fourteen patients were retested after six months. Majority of gait parameters showed significant differences in all experimental conditions when compared between CIDP and HCs. The most consistent findings in CIDP were shorter stride length (SL), prolonged cycle time (CT) and double support time (DS), as well as increased variation of SL and of swing time (ST) (p < 0.05). During follow-up, INCAT improved in nine (64.3%) of 14 patients and MRC-SS improved in eight (57.1%) patients. Six-month changes of CT and its variation during combined task significantly differentiated patients with improved vs. non-improved INCAT (p < 0.05). In conclusion, patients with CIDP had slower gait with prolonged DS and with shorter SL compared to HCs. Increased variation of SL and of ST in CIDP may suggest a potential risk for instability and falls. Shorter CT duration and less CT variation during time correlated well with improvement in disability.